37.1k views
2 votes
1+Sin/Cos + Cos/1+Sin = 2Sec

1+Sin/Cos + Cos/1+Sin = 2Sec-example-1

1 Answer

5 votes

Explanation:

Consider the left-hand side:


(1+sin(\theta))/(cos(\theta)) + (cos(\theta))/(1+sin(\theta))


\:\:\:\:= \frac{(1+sin(\theta))^2 + \cos^2{\theta}}{cos(\theta)(1+sin(\theta))}


\:\:\:\:=\frac{1+2sin(\theta)+\sin^2{\theta} + \cos^2{\theta}}{cos(\theta)(1+sin(\theta))}


\:\:\:\:=(2+2sin(\theta))/(cos(\theta)(1+sin(\theta))) =(2(1+sin(\theta)))/(cos(\theta)(1+sin(\theta)))


\:\:\:\:= (2)/(cos(\theta)) = 2\sec{\theta}

User VerizonW
by
5.8k points